PERENCANAAN DESAIN INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) INDUSTRI TAHU KECAMATAN BATANG KUIS KABUPATEN DELI SERDANG - LUMBAN GAOL, SABAR EBEN EZER; FRANCHITIKA, RIZKY (JURNAL ILMIAH KOHESI, 2024)
Industries in the field of food processing have been established by many Indonesian people, for example the industry owned by Mrs. Amira in Batang Kuis District, Deli Serdang. The industry, which operates for 9 hours by consuming 8,000L of wastewater to produce 400kg of soybeans per day, has produced a lot of liquid waste which, if not properly handled, will pose many adverse risks. Therefore, phytoremediation is needed through the use of water hyacinth with the aim of cleaning polluted or contaminated environments, such as water polluted by chemicals, water hyacinth can absorb, reduce, or break down pollutants in water through the phytoremediation process, helping to restore water quality and the environment naturally. The treatment of liquid waste through WWTP in the tofu industry with the help of water hyacinth will require several media such as infiltration wells, phytoremediation tanks, sedimentation tanks, and equalization tanks. Adjusting the standard of quality requirements for the standard quality value of the effluent in the Minister of Environment and Forestry Regulation No.68 of 2016, the results of the research carried out by the researcher are appropriate because the COD value of the effluent is estimated to reach PH 6; TSS 22.5mg/L; BOD 20.5mg/L; and WWTP 39.5mg/L.